Effect of ERAS-based sputum drainage nursing model on improving postoperative pulmonary function recovery in elderly patients with aneurysmal subarachnoid hemorrhage (基于ERAS模式的排痰护理促进老年蛛网膜下腔出血患者术后肺功能康复效果观察) - CAO Shuonan (曹硕楠); YUAN Qiaoling (袁巧玲); LIU Ranran (刘冉冉) (中西医结合护理)
Objective　Methods 120 elderly patients suffering from aneurysmal subarachnoid hemorrhage and receiving craniotomy from June 2019 to June 2021 were enrolled. Patients were randomly and equally divided into two groups: the traditional group(n=60, who received traditional nursing model) and the ERAS group (n=60, who received ERAS-based sputum drainage nursing model). The expectoration volume, blood oxygen saturation and proinflammatory cytokine level between traditional group and ERAS group were compared. Results At 5th day after intervention, the daily expectoration volume ［(40. 51±9. 25) mL vs. (22. 52±4. 25) mL, P＜0. 01］ and blood oxygen saturation［(94. 52±4. 57)% vs. (84. 25±5. 11)%, P＜0. 01］in the ERAS group were better than those in the traditional group. The percentage of effective expectoration in the ERAS group was higher than that in the traditional group (91. 67% vs, 76. 67%, P＜0. 05). At 5th day after intervention, Patients receiving ERAS-based nursing model had a lower proinflammatory cytokine level (IL-1β, IL- and TNF-α)comparing with patients receiving traditional nursing model (P<0. 01). Conclusion ERAS-based sputum drainage nursing model is helpful for postoperative pulmonary function recovery in elderly patients with aneurysmal subarachnoid hemorrhage and relieve systematic inflammation response. Totally　To investigate the effect of Enhanced Recovery After Surgery( ERAS)-based sputum drainage nursing model on postoperative pulmonary function recovery in elderly patients with aneurysmal subarachnoid hemorrhage. (目的 探讨基于加速康复外科模式(ERAS)的排痰护理促进老年动脉瘤性蛛网膜下腔出血患者术后肺功能康复的效果。方法 招募2019年6月—2021年6月就诊于首都医科大学附属北京天坛医院因动脉瘤性蛛网膜下腔出血行开颅手术治疗且出现肺部感染的老年患者(≥60岁)120例为研究对象, 按照随机抽签法分组。传统组(n=60)接受常规护理干预, ERAS组(n=60)接受基于ERAS模式的排痰护理。比较两组患者的日均排痰量、血氧饱、排痰有效率和度及炎性因子指标。结果 干预后第5天, ERAS组患者的日均排痰量［(40. 51±9. 25) mL vs. (22. 52±4. 25) mL, P＜0. 01］和血氧饱和度［(94. 52±4. 57)% vs. (84. 25±5. 11)%, P＜0. 01］均优于传统组。ERAS组的临床排痰有效率高于传统组, 差异有统计学意义(91. 67% vs. 76. 67%, P＜0. 05)。干预后第5天, ERAS组患者的血清炎症因子(IL-1β, IL-6和TNF-α)水平均低于传统组, 差异有统计学意义(P＜0. 01)。结论 基于ERAS模式的排痰护理有助于老年动脉瘤性蛛网膜下腔出血患者术后肺功能的康复, 缓解患者全身炎症反应, 具有重要临床价值。)